MEANS OF INFLUENCE ON THE MOTIVATION SPHERE OF HIGHER EDUCATION ACQUISITIONS IN CONDITIONS OF SYNCHRONOUS EDUCATION - Пермінова, Людмила (Journal of Information Technologies in Education (ITE), 2024)
In the modern educational paradigm oriented towards the satisfaction of individual requests, the problems of professional formation of future specialists acquire special importance. Social problems, wartime force educators to constantly improve their practical professional skills. Many institutions switched to a distance learning format, and this led to the need to improve work skills with the use of innovative teaching technologies. This has both positive and negative components. The definition and substantiation of means of active learning in the mode of synchronous (asynchronous) learning, which teachers successfully cope with, can be attributed to the positive. However, in connection with remote learning, there is a problem with motivation, the manifestation of independence, and the formation of self-management qualities of higher education students. There is a problem of a positive influence on the motivational sphere of a modern student, which ensures his success both in studies and success in future professional activities. Means of motivation for success should be didactically and methodically coordinated with the needs and individual qualities of those who study. Informatization, digitization of the educational process provides ample opportunities for teachers’ creativity. Modern IT technologies, especially cloud technologies, provide teachers with a fairly convenient, free set of tools for activating the educational and cognitive activities of students, including virtual whiteboards, multimedia presentations, tools for organizing group work, services for creating tests, intelligence cards, supplemented and virtual reality. It should be noted that the quality of information perception, motivation for activity increases when watching videos, listening to texts and musical works. Motivation increases when the winners themselves take an active part in creating drawings, multimedia presentations, etc. The influence on the development of the motivational sphere of higher education seekers is complex and requires a lot of time and effort of teachers.